Polyamines and ethylene interact in mediating the effect of nitrogen rates on synthesis of amino acids in rice grains - Yunji Xu; Shupeng Tang; Chaoqun Jian; Yang Liu; Ke Li; Kuanyu Zhu; Weiyang Zhang; Weilu Wang; Zhiqin Wang; Jianchang Yang (Food and Energy Security, 2022)
Abstract Nitrogen (N) is one of the essential factors influencing amino acid synthesis in rice (Oryza sativa L.) grains. Polyamines (PAs) and ethylene (ETH) play vital roles in grain amino acid biosynthesis of rice. However, knowledge is limited about whether and how PAs and ETH mediate the effect of N rate on amino acid biosynthesis. Two rice cultivars were used with three N rates of low (LN), medium (MN), and high (HN) in the study. Levels of free PAs and ETH, activities/gene expressions of key enzymes related to amino acid synthesis in grains, and the amino acid contents in milled rice were investigated. Free spermidine (Spd) and spermine (Spm) concentrations, especially ratios of free PAs to 1‐aminocylopropane‐1‐carboxylic acid (ACC), and total amino acids (TAAs), essential amino acids (EAAs), and non‐essential amino acids (NEAAs) contents were increased with N rate, while ethylene evolution rate (EER) and ACC concentration were reduced with N increases. There was relatively little difference in the above parameters between MN and HN. Levels of free Spd and Spm, and their ratios to ACC exhibited significant and positive correlations with the activities/gene expressions of key enzymes related to amino acid biosynthesis, and TAAs, NEAAs, and EAAs contents, whereas ACC and EER levels had significantly negative correlations with those parameters. Exogenous Spd, Spm, or AVG (an ETH synthesis inhibitor) increased the enzymatic activities and gene expressions, whereas MGBG (a Spd or Spm synthesis inhibitor) or ethephon (an ETH‐releasing agent) exerted the opposite effect. These results demonstrated that free PAs and ETH antagonistically interact in mediating the effect of N rate on grain amino acid synthesis of rice. Higher ratios of free PAs to ACC could promote synthesis of amino acids in grains of rice.